Genetic and morphological means of differentiating within and between populations of Widdringtonia whytei and Widdringtonia nodiflora on Mount Mulanje, Malawi - Hall, Stuart (Department of Biological Sciences, 2017)
There has been confusion in the past as to the taxonomy of Widdringtonia on Mount Mulanje. At present it is accepted that there are two species present. The aim of this study was to assess the level of genetic variation present across six populations of Widdringtonia whytei and Widdringtonia nodijlora on the mountain, and determine whether there are two genetically separate species present. Analysis of genetic variation included PsbA (chloroplast DNA), ITS (nuclear DNA), microsatellite and ISSR gene region markers. Out of the markers that amplified successfully, it was found that there is little genetic variation present with no differentiation between or within taxonomic groups for the gene regions analyzed. Morphometric analysis of cones and leaves grouped W. whytei and W. nodijlora separately, with a midgroup more closely associated with definite W. whytei. This compared favourably with observations of individuals from the different groups in the field. It is suggested that based on the low level of genetic variation across the mountain, W. whytei and W. nodijlora have diverged very recently from a W. nodijlora ancestor.